Seven brief lessons on physics - Rovelli, Carlo, 1956- (Penguin Random House, 2016)
'Here, on the edge of what we know, in contact with the ocean of the unknown, shines the mystery and the beauty of the world. And it's breathtaking' These seven short, simple lessons guide us through the scientific revolution that shook physics in the twentieth century and still continues to shake us today. Theoretical physicist Carlo Rovelli, a founder of the loop quantum gravity theory. explains Einstein's theory of general relativity, quantum mechanics, black holes, the complex architecture of the universe, elementary particles, gravity, and the nature of the mind. In under eighty pages, readers will understand the most transformative scientific discoveries of the twentieth century and what they mean for us.